2022
DOI: 10.3390/su141710564
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Biodiversity in Tabuk Region of Saudi Arabia: A Comprehensive Review

Abstract: Biodiversity refers to all of the all types of species in one geographical region or ecosystem. It consists of plants, animals, bacteria, and other life forms. As an estimate, around 1.7 million species are on record globally and approximately 15,000–18,000 new species are added each year. Global climate change is accelerating species extinction due to habitat destruction. Further, various abiotic and biotic environmental factors are limiting the pattern of biodiversity in a geographical region. A change in sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The post-interpretation process included the development of LULC maps and the identification of their alterations. In the current study, the categorization assessment was employed as a method of change detection [50][51][52][53][54][55][56][57][58][59][60][61]. After that, the overlay images of land use and land cover over the past 35 years were put into an adjustment matrix.…”
Section: Digital Image Processing Inventory and Assessmentmentioning
confidence: 99%
“…The post-interpretation process included the development of LULC maps and the identification of their alterations. In the current study, the categorization assessment was employed as a method of change detection [50][51][52][53][54][55][56][57][58][59][60][61]. After that, the overlay images of land use and land cover over the past 35 years were put into an adjustment matrix.…”
Section: Digital Image Processing Inventory and Assessmentmentioning
confidence: 99%
“…Weeds are considered one of the plant parasites that interfere with economic crop growth and development and cause eventually significant yield loss (Abdallah et al, 2021;Ansari et al, 2022;Khamare et al, 2022). Weeds compete with crops on light, nutrients, water, and space that diminishes crop growth and yield.…”
Section: Introductionmentioning
confidence: 99%
“…Al Mutairi [9] reported one hundred and sixty-three species assigned to fortyone families at five sites (Aldesah, Alzetah, Alawz, Harra and Sharma). Ansari et al [18] have estimated the identified species cited in the different studies of Tabuk and mentioned two hundred twenty-seven species in their comprehensive review. These species belonged to 157 genera and 45 angiosperms' families, including 12 endangered species.…”
Section: Introductionmentioning
confidence: 99%